Putting guidelines into practice: Using co‐design to develop a complex intervention based on NG48 to enable care staff to provide daily oral care to older people living in care homes. (14th March 2022) - Langley, Joe; Wassall, Rebecca; Geddis‐Regan, Andrew; Watson, Sinead; Verey, Anna; McKenna, Gerald; Brocklehurst, Paul; Tsakos, Georgios
Abstract: Objectives: (1) Explore the challenges of providing daily oral care in care homes; (2) understand oral care practices provided by care home staff; (3) co‐design practical resources supporting care home staff in these activities. Methods: Three Sheffield care homes were identified via the "ENRICH Research Ready Care Home Network, " and three to six staff per site were recruited as co‐design partners. Design researchers led three co‐design workshops exploring care home staff's experiences of providing daily oral care, including challenges, coping strategies and the role of current guidelines. New resources were prototyped to support the use of guidelines in practice. The design researchers developed final resources to enable the use of these guidelines in‐practice‐in‐context. Findings: Care home staff operate under time and resource constraints. The proportion of residents with dementia and other neurodegenerative conditions is rapidly increasing. Care home staff face challenges when residents adopt "refusal behaviours" and balancing daily oral care needs with resident and carer safety becomes complex. Care home staff have developed many coping strategies to navigate "refusal behaviours." Supporting resources need to "fit" within the complexities of practice‐in‐context. Conclusions: The provision of daily oral care practices in care homes is complex and challenging. The co‐design process revealed care home staff have a "library" of context‐specific practical knowledge and coping strategies. This study offers insights into the process of making guidelines usable for professionals in their contexts of practice, exploring the agenda of implementing evidence‐based guidelines.